Communicating the Past in the Digital Age: Proceedings of the International Conference on Digital Methods in Teaching and Learn 2020
DOI: 10.5334/bch.e
|View full text |Cite
|
Sign up to set email alerts
|

An Inclusive Prehistory Game by the Blind and Visually Impaired . Creating an Inclusive App Game on Prehistoric Archaeology with the BSVN e.V. for the Permanent Exhibition of the Neanderthal Museum

Abstract: Can an app game make a museum exhibition on prehistoric archaeology more accessible for guests with visual impairments? This is the research question of the NMsee project, a cooperative undertaking of BSV Nordrhein e.V. and the Neanderthal Museum in North Rhine Westphalia, Germany. Archaeological

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In line with affordability and practicality concerns, the [18] project focused on developing cost-effective smart glasses designed for reading signs, a key aid facilitating blind people's move towards autonomy, and thus making strides toward widespread inclusionary practices. The study presented in [19] delved into the creation of a Prehistory Game aimed at VI audiences, focusing on the effectiveness of museum accessibility improvements obtained via audio-centric app games featuring user-friendly designs, a notable endeavour towards enriching cultural experiences amongst visually disadvantaged communities.…”
Section: Exploring the Potential Of Xr As An Educational Assistive Te...mentioning
confidence: 99%
See 2 more Smart Citations
“…In line with affordability and practicality concerns, the [18] project focused on developing cost-effective smart glasses designed for reading signs, a key aid facilitating blind people's move towards autonomy, and thus making strides toward widespread inclusionary practices. The study presented in [19] delved into the creation of a Prehistory Game aimed at VI audiences, focusing on the effectiveness of museum accessibility improvements obtained via audio-centric app games featuring user-friendly designs, a notable endeavour towards enriching cultural experiences amongst visually disadvantaged communities.…”
Section: Exploring the Potential Of Xr As An Educational Assistive Te...mentioning
confidence: 99%
“…Ref. [67] found that head-mounted displays were effective for individuals with low vision seeking immersive experiences, while [19] emphasised the inclusivity of a prehistory game for the VI in a museum exhibition. Additionally, Ref.…”
Section: Academic Disciplinementioning
confidence: 99%
See 1 more Smart Citation